Redistribution of the soil 137Cs inventory through litter and sediment transport on a hillslope covered by deciduous forest in Fukushima, Japan. Issue 10 (10th May 2022) - Oda, Tomoki; Hotta, Norifumi; Miura, Satoru; Endo, Izuki; Tanoi, Keitaro; Renschler, Chris S.; Ohte, Nobuhito
Abstract: The long‐term behaviour of radiocaesium ( 137 Cs) activity concentrations in forest ecosystems and their downstream impacts remain important issues in the deciduous broadleaf forests of Fukushima, Japan following the Fukushima Daiichi Nuclear Power Plant accident. To predict 137 Cs cycling and discharge in the forest ecosystem, it is important to understand the spatial dynamics of the 137 Cs inventory and transport along hillslopes. Therefore, we observed the spatial distribution of the 137 Cs inventory and 137 Cs transport via sediment and litter of a deciduous forest hillslope in Fukushima, Japan in 2016 and 2017 and examined how the spatial distribution of 137 Cs inventory was formed using a mass balance model. In 2017, the 137 Cs activity concentration was significantly greater in the downslope riparian area (455 kBq/m 2 ) than in the upslope ridge area (179 kBq/m 2 ). Annual 137 Cs transport within litter and sediment contributed <0.5% to the current 137 Cs inventory and cannot explain the current spatial variation of 137 Cs inventory on the hillslope. The mass balance model results showed that if the initial 137 Cs deposition was distributed uniformly in 2011, the spatial distribution of the hillslope 137 Cs inventory was influenced mainly by the movement of leaf litter with a high 137 Cs activity concentration. Abstract : We examined spatiotemporal changes in the 137 Cs inventory on a hillslope covered by deciduous forest. The 137 Cs inventory was greater on the lower slope than on the upper slope. The observed 137 Cs transport via sediment and litter and the mass balance model results indicated that spatial distribution of the hillslope 137 Cs inventory was influenced mainly by the movement of leaf litter with a high 137 Cs activity concentration.